2014
DOI: 10.1051/0004-6361/201424037
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Mira-like tail and bow shock about the semi-regular variable V CVn from four decades of polarization measurements

Abstract: Polarization is a powerful tool for understanding stellar atmospheres and circumstellar environments. Mira and semi-regular variable stars have been observed for decades and some are known to be polarimetrically variable, however, the semi-regular variable V Canes Venatici displays an unusually large, unexplained amount of polarization. We present ten years of optical polarization observations obtained with the HPOL instrument, supplemented by published observations spanning a total interval of about forty yea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Because we have considered spherical grains only, our simulations are less applicable to cases where magnetic fields likely play a role in aligning dust grains, such as the Galactic Center sources studied by Buchholz et al (2011Buchholz et al ( , 2013, but they may still provide useful insights. For systems with large polarization magnitudes such as V CVn (Neilson et al 2014) or the DSO (Shahzamanian et al 2016;Zajaček et al 2017b), our simulations provide lower limits to the observed polarization that can guide future modeling by diagnosing the presence of more complex circumstellar structures. In all cases, we find the most useful constraints are possible with polarization observations at multiple wavelengths, and encourage observers to make this a standard practice.…”
Section: Unresolved Bow Shockmentioning
confidence: 94%
See 1 more Smart Citation
“…Because we have considered spherical grains only, our simulations are less applicable to cases where magnetic fields likely play a role in aligning dust grains, such as the Galactic Center sources studied by Buchholz et al (2011Buchholz et al ( , 2013, but they may still provide useful insights. For systems with large polarization magnitudes such as V CVn (Neilson et al 2014) or the DSO (Shahzamanian et al 2016;Zajaček et al 2017b), our simulations provide lower limits to the observed polarization that can guide future modeling by diagnosing the presence of more complex circumstellar structures. In all cases, we find the most useful constraints are possible with polarization observations at multiple wavelengths, and encourage observers to make this a standard practice.…”
Section: Unresolved Bow Shockmentioning
confidence: 94%
“…An additional 𝐾-band observation of this object would allow more robust conclusions. Neilson et al (2014) proposed that an unresolved stellar wind bow shock could explain the large 𝑉-band intrinsic polarization (𝑝 𝑉 ≈ 1 − 6%) in the semi-regular variable V CVn. These authors attributed the time variability of their polarization measurements to pulsation-related variability in the density of the stellar wind.…”
Section: Unresolved Bow Shockmentioning
confidence: 99%
“…In addition, V CVn exhibits most prominent inverse correlation between flux and fraction of polarization among other long-period variables. Neilson et al (2014) discussed the polarization variability of V CVn in detail. They considered qualitatively several hypotheses which can potentially describe unique behavior of the star.…”
Section: Introductionmentioning
confidence: 99%
“…For unresolved bow shocks (or cases in which a bow shock is predicted to exist, e.g. Neilson et al 2014), we measure a single polarization value corresponding to a single viewing angle. This corresponds to a horizontal line in figures such as Figs.…”
Section: Observational Implicationsmentioning
confidence: 99%
“…SLIP can also produce position angle maps for comparison with observations. The position angles in our models are consistently ≈ 0 • for most viewing angles, but flip to near 90 • at high inclinations and optical depths when q is negative.For unresolved bow shocks (or cases in which a bow shock is predicted to exist, e.g Neilson et al 2014…”
mentioning
confidence: 99%